Macroscopic tumor volume of malignant glioma determined by contrast-enhanced magnetic resonance imaging with and without magnetization transfer contrast - Hawighorst, Hans; Schreiber, Wolfgang; Knopp, Michael V.; Essig, Marco; Engenhart, Rita; Brix, Gunnar; Kaick, Gerhard van (Magnetic resonance imaging, 1996)
The purposes of this study were to compare the conspicuity and lesion volume of contrast-enhancing macroscopic malignant glioma determined by postcontrast magnetic resonance (MR) imaging with and without magnetization transfer (MT) saturation, and to discuss possible implications for radiotherapy planning. Nineteen patients (age 24-60 years) with histologically proven malignant glioma were prospectively examined by MR imaging. After the administration of gadolinium dimeglumine (0.1 mmol/kg body weight), the lesions were imaged with an MT-weighted FLASH (fast, low-angle shot) pulse sequence and with a conventional T1-weighted spin-echo (SE) sequence without MT saturation. The mean tumor volumes of gliomas measured on MT-weighted FLASH images were significantly (p < .01) larger than those obtained from T1-weighted SE images (45 ± 15 cm3 vs. 33 ± 10 cm3). The mean contrast-to-noise ratio of enhancing lesions on MT-weighted FLASH was 48 ± 14 compared with 30 ± 14 on SE images, representing a significant (p < .01) improvement. We conclude that the volume of contrast enhancement of malignant glioma identified on MT-weighted FLASH images represents the area of disrupted blood-brain barrier. If this volume of subtle contrast enhancement is caused by tumor infiltration and represents the boost target volume for stereotactic radiosurgery or brachytherapy, MT-weighted FLASH images would be better than T1-weighted SE images to define these volumes. These improved delineation of areas at highest risk for recurrence following radiation therapy should enhance the efficacy of treatment planning for high-boost therapy.